Business Strategy Improvement for SuperApp BTN Mobile - Raihan Rasyidi (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
The development of digital technology has entered all lines of life in society, so that the distance between regions is no longer a barrier between one region and another. This factor makes all companies try to use the internet as a penetration material for company activities in marketing their products and services. Because by using the internet companies can make marketing cost efficiencies, cost efficiencies in opening new branches, HR costs and company operational costs. The world's advancements in information and communication technology (internet) have influenced changes in lifestyle and consumer behavior, so advancements in information and communication technology-based industries have become a requirement that seems inseparable from human life. Additionally, this affects consumer expectations for the company's products and services.